(untitled) (Raparin Journal of Humanities (RJH), 2022)
These pages are the great scholar Ibrahim bin Hassan bin Shihab Al-Din Al-Gorani Al-Shahrazuri Al-Shahrani Al-Kurdi Al-Shafi’I’s, the great mujtahid (Scholar) and Imam. He was born in 1025 HD/AD and grew up and brought in pure chastity family that gave birth many great scientists. In addition to the role of his scientific family in which he grew up. He began to study the Holy Qur’an in his family, and after completing it, he began to study Arabic sciences in the presence of the greatest Scholars of his country. Then he occupied himself with studying the rational sciences, such as logic, theology, philosophy, engineering, astronomy and arithmetic. He also heard the science of hadith from of a group of scholars in different places outside of his country, such as the Levant, Egypt, the Hijaz and, especially, in both Sacred Mosque and Prophetic Mosque. He mentioned his sheikhs who were from different countries and nations and wrote a bography about everyone of them, such Safi Ahmed bin Muhammed Al-Qashashi, ِAbi Al-mawahib Ahmed bin Ali Al-sh’inawi .But he did not mention his Kurdish master’s, except Mala Muhammed Sharif Al-Sidqi Al-Gorani, and The master Abdulkareem bin Mala Abibakr Al-Musannif. He also travlled to Al-Madinah Al-Monawarah, stayed there and studied at group of its scholars to take different scienes from them. His habit was when he was asked a question about any sciences that he was familiar with, he was mastered with the utmost perfection. He had many works. It was even said he had about eighty useful books and letters in the whole Islamic sciences. Such Al-hadith, exegesis, jurisprudence, theology, philosophy, Sufism, and linguistics. In this his letter stated the ruling of someone is preceded the Imam In the status of bending in prayer and the Imam believed there is not any prevents of it, Does his prostration is taken into consideration or not? In his answer, he stated that the certainty means doubt, it means if he has dominance that he reached the prostration that regards as prostration, otherwise, it never taken in the cansideration as prostration. He stated the imam Al-Rafie, Al-Shekh Ibn Al-Hajer and Alfariqy’s opinions about the situation.